Суперкомпьютеры: тенденции и технологии последнего двадцатилетия - Клименко, В.П.; Комухаев, Э.И. (Математичні машини і системи, 2006)
В статье рассмотрены вопросы тенденций, архитектур, технологий разработок суперкомпьютеров последнего двадцатилетия (1986 - 2006 гг.). Приведены данные о новых возможностях элементной базы суперкомпьютеров, о расширении применений. Акцентированы перспективы развития кластерных систем, пути совершенствования взаимодействия узлов кластеров. Отмечен значительный вклад ведущих специалистов институтов Кибцентра им. В.М. Глушкова НАНУ в разработки решений и технологий реализации суперкомпьютеров. В статті розглянуто питання тенденцій, архітектур, технологій розробок суперкомп'ютерів останнього двадцятиліття (1986 - 2006 рр.). Наведено дані про нові можливості елементної бази суперкомп'ьютерів та про розширення застосувань. Акцентовано перспективи розвитку кластерних систем, шляхи вдосконалення взаємодії вузлів кластерів. Відмічено значний внесок провідних фахівців інститутів Кібцентру ім. В.М. Глушкова НАНУ в розробки рішень та технології реалізації суперкомп'ютерів. The problems of tendencies, architectures, technology of the developments of the supercomputers of the last twentieth anniversary are discussed in the paper. There are adduced data about new abilities of the element base of the supercomputers, about broadening of using. The prospects of the development of cluster systems, the ways of perfection of interaction of the cluster nodes are accepted. The significant contribution of the leading specialists of the Institutes of Cybernetic Centre by Glushkov V.M. of NASU to the developments of decisions and technologies of supercomputers realisation is marked.